The measurement scale of resilience among family caregivers of children with cancer: a psychometric evaluation - Filiberto Toledano-Toledano; José Moral de la Rubia; Yunier Broche-Pérez; Miriam Teresa Domínguez-Guedea; Víctor Granados-García (BMC, 2019)
Abstract Background Resilience to disease is a process of positive adaptation despite the loss of health, it involves the development of vitality and skills to overcome the negative effects of adversity, risks, and vulnerability caused by disease. In Mexico, cancer is the leading cause of death in children. Both the diagnosis and the treatment of childhood cancer affect the health of family caregivers. However, resilience is a personality trait that can be protective in these situations. Therefore, resilience is an important psychological construct to measure, evaluate and develop in specific populations and contexts. In Mexico, a scale to assess this trait has been developed. This study aimed to test the reliability and factor structure of the Mexican Measurement Scale of Resilience (RESI-M), describe its distribution, evaluate its relationship with sociodemographic variables, and verify its concurrent validity with psychological well-being, depression, anxiety and parental stress and its independence from social desirability. Methods A cross-sectional study was conducted involving an intentional nonprobability sample of 330 family caregivers of children with cancer hospitalized at the National Institute of Health in Mexico City. The participants responded to a sociodemographic variables questionnaire, the Mexican Measurement Scale of Resilience RESI-M, and five other assessment scales. Results Overall internal consistency was very high (ordinal alpha = .976). The confirmatory factor analysis demonstrated that the five-factor model had a close fit to the data: NFI = .970, CFI = .997, SRMR = .055, and RMSEA = .019. The distributions of the RESI-M total score followed a normal distribution. The RESI-M total score correlated positively with psychological well-being and negatively with depression, parental stress and anxiety. The overall RESI-M total score also correlated positively with age, but there was no difference in means between women and men. Resilience was independent of social desirability. Conclusions The RESI-M shows reliability and construct validity in family caregivers of children with cancer and does not show a bias in relation to social desirability.